Infection and inflammation in schizophrenia and bipolar disorder. (February 2017) - Tanaka, Teppei; Matsuda, Taro; Hayes, Lindsay N.; Yang, Shuojia; Rodriguez, Katrina; Severance, Emily G.; Yolken, Robert H.; Sawa, Akira; Eaton, William W.
Highlights: Bipolar patients showed increased soluble CD14 and C-reactive protein in plasma. Schizophrenia patients showed increased soluble CD14 in plasma. Bipolar patients had increased levels of antibodies for CMV IgM and HSV-2 IgG. Cognitive function and CMV IgG level were negatively correlated in bipolar patients. Abstract: The present study investigated the relationship between exposure to infectious agents and inflammation markers in individuals with schizophrenia (SZ), bipolar disorder (BP), and controls without a psychiatric disorder. We measured plasma levels of antibodies and innate immune markers and correlated them with clinical symptoms and cognitive function. In both SZ and BP, we found an increase in soluble CD14, and in BP an increase in C-reactive protein, IgM class antibodies against cytomegalovirus (CMV), and IgG class antibodies against herpes simplex virus 2. Furthermore in BP, we observed a negative relationship between IgG antibodies against CMV and scores for cognitive function.